Effects Of Guest Experience, Well-Being, And Altruism On Resort Hotel Guests’ E-Word-Of-Mouth Intention In China - Yedan, Fan (2024)
This study integrated the Experience Economy model and positive psychology into the stimulus-organism-response (SOR) schema to predict guests’ eWOM intention in China. Specifically, entertainment experience, education experience, esthetic experience and escapism experience served as stimuli, hedonic well-being and eudaimonic well-being were applied as organism, which ultimately led to eWOM intention as behavioural response.